Book Review - Strategic Healthcare Management: Planning and Execution by Stephen L. Walston - Vernando Yanry Lameky (ACHSM, 2024)
Strategic health service management combines aspects of traditional management with an emphasis on long-term strategies and adaptation to dynamic changes in the health environment [1]. It aims to improve service quality, operational efficiency, and overall population health results [2, 3]. This is what was explored by Walston (2023) in his book Strategic Healthcare Management: Planning and Execution, Third Edition.....